2010
DOI: 10.1002/pssc.200983375
|View full text |Cite
|
Sign up to set email alerts
|

FeCoBSiNb bulk metallic glasses with Cu additions

Abstract: The effect of Cu additions (1, 2 and 3 at.%) on the glass forming ability (GFA) and magnetic properties of [(Fe0.5Co0.5)0.75Si0.05B0.20]96Nb4 is studied. As the Cu content increases, the GFA deteriorates. The structure of the samples, as well as the crystallization behavior was in‐situ studied by means of synchrotron beam. The as‐cast 1 mm diameter rods are characterized by a mixture of (nano)‐crystals and amorphous matrix. Upon heating, the pre‐existing nuclei grow, without forming new crystalline phases. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…It was argued that copper additions can stimulate nucleation of α-Fe and effectively refine the α-Fe grain sizes to 20 nm or below. Although these Cu-containing Fe-based metallic glasses have a large saturation magnetization close to that of the conventional Fe-Si alloys, their GFA is reduced and the maximum attainable size is limited to the micrometer level1415161718192021, which is consistent with the results in the Fe-Co-based alloys222324. In our study, however, we surprisingly found that minor doping of the element Cu is actually very effective in destabilizing the α-Fe nano-clusters and promoting the GFA.…”
supporting
confidence: 80%
“…It was argued that copper additions can stimulate nucleation of α-Fe and effectively refine the α-Fe grain sizes to 20 nm or below. Although these Cu-containing Fe-based metallic glasses have a large saturation magnetization close to that of the conventional Fe-Si alloys, their GFA is reduced and the maximum attainable size is limited to the micrometer level1415161718192021, which is consistent with the results in the Fe-Co-based alloys222324. In our study, however, we surprisingly found that minor doping of the element Cu is actually very effective in destabilizing the α-Fe nano-clusters and promoting the GFA.…”
supporting
confidence: 80%
“…Other studies showed that a ternary Ti-Nb-Zr alloy has improved stability of the surface films exhibiting exceptionally high resistance to oxidizing acids 39,43 . Some reports showed the role of Si in the stabilizing the crystallized phases in Si-Nb-based alloys that might be helpful to promote corrosion resistance [67][68][69][70] . It has been also reported that the addition of Si can improve the corrosion resistance of Ti alloys in acidic solutions due to the formation of stable SiO2 and Si-doped TiO2 passive layers on the Ti-Si alloy 34,71 .…”
mentioning
confidence: 99%
“…However, the H c increased rapidly and the B s began to decrease upon the emergence of Fe 3 (B,P), resulting from annealing at T a of 783 K or higher. Table 1 lists the GFA (D cr ) and Magnetic Properties (H c , B s , and µ e ) of the alloys developed in this work and some other Fe-based bulk nanocrystalline alloys widely reported previously [1,9,13]. The developed FeSiBPNbCu bulk nanocrystalline alloys with minor Nb addition show comprehensively excellent properties, especially for the combination of high GFA and high B s , namely, D cr of 1-2.5 mm and high B s of 1.42-1.5 T, but also low H c of 0.86-2 A/m, high µ e at 1 kHz of 15,000-18,500.…”
Section: Resultsmentioning
confidence: 99%
“…Some attempts have been made to synthesize Fe-based bulk nanocrystalline alloys with high GFA and SMPs. Resultantly, a series of alloys have been successfully developed [12][13][14][15][16][17][18], which can be made into thick ribbons or nanocrystalline rod-shaped samples. Recently, by logically adding Cu, FeSiBPNbCu alloys with high GFA and SMPs were successfully developed by our team [18].…”
Section: Introductionmentioning
confidence: 99%